2022
DOI: 10.1111/jog.15367
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging characteristics of polypoid endometriosis and review of the literature

Abstract: Aim: Polypoid endometriosis is a rare variant of endometriosis and may mimic malignancy. The purpose of this study is to evaluate magnetic resonance (MR) imaging characteristics of polypoid endometriosis for the differential diagnosis with malignancy. Methods: MR imaging findings of four histologically proven polypoid endometriosis were retrospectively evaluated with the review of the literature. Results: All polypoid endometriosis exhibited high signal intensity on T2-weighted images reflecting abundant dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…However, few recent imaging studies help us to narrow the diagnosis. According to Takeuchi et al [6], polypoid endometriosis showed high signal intensity on T2-weighted images. Peritoneal lesions were associated with pelvic endometriosis and peripheral low-intensity rims were observed as "black rim sign" which is also noticed in this case [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, few recent imaging studies help us to narrow the diagnosis. According to Takeuchi et al [6], polypoid endometriosis showed high signal intensity on T2-weighted images. Peritoneal lesions were associated with pelvic endometriosis and peripheral low-intensity rims were observed as "black rim sign" which is also noticed in this case [6].…”
Section: Discussionmentioning
confidence: 97%
“…Many radiologic findings are suggested to help to make the differential diagnosis of polypoid endometriosis, but a histopathologic exam of the specimen obtained through surgery is still crucial and the only way to rule out malignancy [6].…”
Section: Discussionmentioning
confidence: 99%